Tissue culture for the rapid clonal propagation of Aloe barbadensis Miller - Marfori, Eufroncio C. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2005)
Aloe barbadensis, one of the world's most widely used substances for medicine, cosmetics and food, is vegetatively propagated using the suckers. This conventional method is very slow and could not meet the required number of planting materials needed to establish a large-scale plantation. An alternative propagation method is by tissue culture. Nodal explants of A. barbadensis were placed in Murashige and Skoog (MS) medium containing different levels of kinetin or 6-benzylaminopurine (BAP) to induce multiple shoot formation. The best treatment for multiple shoot induction was 1 mg L-1 BAP, which produced an average of 11 shoots per explant in 1 mo. Individual shoots from the multiple shoot clumps were taken and transferred in MS medium containing different levels of indole-3-acetic acid (IAA), indole-3-butyric acid (IBA) or α-naphthaleneacetic acid (NAA) for rooting. The best auxin for root formation was NAA, with an optimum concentration of 0.10 mg L-1. Rooted plantlets were successfully transferred in the field.